Biosynthesis and Transport of Nucleotide Sugars for Plant Hemicellulose - Zhang, Wenjuan; Qin, Wenqi; Li, Huiling; Wu, Ai-min (Frontiers in Plant Science, 2021)
Hemicellulose is entangled with cellulose through hydrogen bonds, meanwhile acts as a bridge for the deposition of lignin monomer in the secondary wall. Therefore, hemicellulose plays a vital role in the utilization of cell wall biomass. Many advances in hemicellulose research have recently been made, and a large number of genes and their functions have been identified and verified. However, due to the diversity and complexity of hemicellulose, the biosynthesis and regulatory mechanisms are yet unknown. In this review, we summarized the types of plant hemicellulose, the specific hemicellulose nucleotide sugar substrates, the relative key transporters and the biosynthesis pathways, etc., which will contribute to regulate the synthesis of hemicellulose in the future.